2011
DOI: 10.1097/maj.0b013e31821d9905
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Chronic Liver Disease: Relationship Between Peripheral and Hepatic Measurements

Abstract: Introduction Oxidative stress plays an important role in the pathogenesis of many liver diseases. Investigators often measure markers of oxidative stress in peripheral veins as a reflection of hepatic oxidative stress as it is not always feasible to measure oxidative stress in liver tissue. However, it is unknown whether markers of oxidative stress measured from peripheral sites accurately reflect hepatic tissue oxidative stress. The aim of this study is to examine the relationship of oxidative stress marker a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 19 publications
(18 reference statements)
0
17
1
Order By: Relevance
“…Disparate values in the level of MDA in groups with or without HRS, correlate with the level of fibrosis and the level of inflammation in liver cirrhosis [ 27 ]. Unlike our results, a study by Vuppalanchi [ 28 ] showed that MDA correlated poorly with hepatic tissue oxidative stress. Generally, alcohol is metabolized in the liver by ADH pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…Disparate values in the level of MDA in groups with or without HRS, correlate with the level of fibrosis and the level of inflammation in liver cirrhosis [ 27 ]. Unlike our results, a study by Vuppalanchi [ 28 ] showed that MDA correlated poorly with hepatic tissue oxidative stress. Generally, alcohol is metabolized in the liver by ADH pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…Maintaining cellular redox homeostasis is a major challenge in any biological system to prevent lipid peroxidation, membrane damage and DNA mutations (38). Upon exposure to the released free radicals, the lipid layer in the cell membrane undergoing peroxidation and oxidative destruction of polyunsaturated fatty acids (arachidonic acid) of the cell membranes, which have dire consequences effects on cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Markers of oxidative stress measured from the peripheral venous samples is poorly reflective of hepatic tissue oxidative stress. Therefore, we measured oxidative stress markers in liver tissue [36]. It is wellknown that HBO administration increases both ROS formation and antioxidant enzymes [37].…”
Section: Discussionmentioning
confidence: 99%